Combination of hydrothermodynamic (HTD) processing and different drying methods for natural blueberry leather. (January 2018) - Chen, Yougui; Martynenko, Alex
Abstract: The effects of two-stage fruit processing on the quality of natural blueberry leather are reported. Different combinations of pureeing methods, including hydrothermodynamic vs. conventional blending and drying technologies, including freeze, forced-air and electrohydrodynamic drying, were studied. At the first stage, hydrothermodynamic processing provided better quality compared to conventional blending due to full enzymes inactivation and less degradation of bioactive compounds. This was beneficial for the next stage of drying, where hydrothermodynamic processed puree did not degrade under forced-air drying below 65 °C, while conventional blended puree demonstrated rapid degradation of anthocyanin (23% loss) and formation of polymeric colour (20%). Electrohydrodynamic drying showed partial inactivation of enzymes, but negatively affected leather quality (15.6–20.6% loss of anthocyanin, 17.3–27.9% loss of polyphenols), which may be due to oxidation by ozone, generated in corona discharge. The current study suggested hydrothermodynamic pureeing for inactivation of enzymes and forced-air drying at 65 °C for maximum preservation of nutritional quality. Highlights: HTD pureeing completely inactivates enzymes resulting in less quality degradation. AD drying at 50 °C of conventionally blended puree resulted in significant quality loss. EHD drying showed positive effect on enzymes inactivation, but negative effect on puree quality. Two-stage process with HTD pureeing and AD drying at 65 °C is recommended for natural leather production.